2011
DOI: 10.3892/ol.2011.421
|View full text |Cite
|
Sign up to set email alerts
|

A polymorphism in the nuclear receptor coactivator 7 gene and breast cancer susceptibility

Abstract: Abstract. The nuclear receptor coactivator 7 (NCoA7) gene codes for an estrogen receptor-associated protein that plays a significant role in the cellular response to estrogens. Given that NCoA7 is expressed in the mammary gland, alterations in this gene may affect breast cancer risk. In this study, we compared the genotype and allele frequencies of the missense single nucleotide polymorphism (SNP) rs1567, located in the coding region of the NCoA7 gene and resulting in an amino acid exchange from asparagine to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Although NCOA7 can be recruited to the promoter region of ERα target genes following estradiol treatment, NCOA7 has a lesser extent of sequence and structure homology with other coactivators, including those belonging to the SRC family, and might function as a distinct coactivator class (46). Several gene polymorphisms of NCOA7 have been associated with the development of breast cancer (64, 65). In another study, NCOA7 was identified as a potential biomarker in oral squamous cell carcinoma (53).…”
Section: Discussionmentioning
confidence: 99%
“…Although NCOA7 can be recruited to the promoter region of ERα target genes following estradiol treatment, NCOA7 has a lesser extent of sequence and structure homology with other coactivators, including those belonging to the SRC family, and might function as a distinct coactivator class (46). Several gene polymorphisms of NCOA7 have been associated with the development of breast cancer (64, 65). In another study, NCOA7 was identified as a potential biomarker in oral squamous cell carcinoma (53).…”
Section: Discussionmentioning
confidence: 99%
“…Relatively little is known regarding the involvement of NCOA7 in tumorigenesis. It is shown by genome-wide association studies that several gene polymorphisms of NCOA7 were associated with the development of breast cancer [ 31 , 32 ]. Recently, individual studies demonstrated that NCOA7 regulated all-trans-retinoic acid (ATRA)-mediated neuronal differentiation and functioned as a favourable prognostic indicator for neuroblastoma [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…S3J). Interestingly, NCOA7 (Nuclear Receptor Coactivator 7) has been reported to have gene polymorphisms associated with breast cancer development [26,27] and it has also been identified as a potential biomarker in oral squamous cell carcinoma [28]. In addition, the engagement of NCOA7 by 3-HAA (3-hydroxyanthranilic acid) enhances the activation of AhR (aryl hydrocarbon receptor) in immunoregulatory dendritic cells [29].…”
Section: Risk Score Serves As a Risk Factor For Overall Survival In T...mentioning
confidence: 99%